Laminated film roll and film laminate roll using the same

The laminated film structure with an anchor and inorganic layer on a base film with controlled expansion coefficients addresses heat-induced deterioration, ensuring effective gas barrier and adhesion for various applications.

JP7615541B2Active Publication Date: 2025-01-17MITSUBISHI CHEM CORP
View PDF 17 Cites 0 Cited by

Patent Information

Application Number
JP2020072329
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-04-14
Publication Date
2025-01-17
Estimated Expiration
2040-04-14

AI Technical Summary

Technical Problem

Existing gas barrier laminated films with inorganic layers suffer from deterioration in gas barrier properties when exposed to heat, particularly when using base films with poor heat resistance such as polylactic acid or polyolefin films.

Method used

A laminated film structure is developed with an anchor layer and an inorganic layer sequentially laminated on a base film, maintaining a controlled average linear expansion coefficient within specific ranges to prevent cracking during heat treatment, ensuring good adhesion and gas barrier properties.

Benefits of technology

The laminated film roll maintains desired gas barrier properties and adhesion even when subjected to heat, suitable for packaging and applications like liquid crystal display elements, solar cells, and electromagnetic shields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007615541000001
    Figure 0007615541000001
  • Figure 0007615541000002
    Figure 0007615541000002
Patent Text Reader

Abstract

To provide a laminated film assembled with an anchor layer and an inorganic layer on one side of a substrate film and capable of achieving higher gas barrier property and a manufacturing method thereof, and a film laminate using the laminated film.SOLUTION: A laminated film roll includes a laminated film assembled with an anchor layer and an inorganic layer laminated successively at least on one side of a substrate film (1) and has an average linear expansion ratio by a thermomechanical analysis (TMA) at 105-120°C of -7×10-4-0 / °C in a longer direction and of -1×10-3-0 / °C in a width direction.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminated film roll having excellent gas barrier properties, and a film laminate roll using the same. [Background technology]

[0002] 2. Description of the Related Art Gas barrier laminate films having a plastic film substrate and a layer (referred to as an "inorganic layer") mainly made of an inorganic material, such as an inorganic oxide vapor deposition layer, formed on the surface of the substrate have been widely used for packaging items that require protection against various gases, such as water vapor and oxygen, for example, for packaging to prevent deterioration of food, industrial products, pharmaceuticals, etc. In addition to packaging applications, new applications of this gas barrier laminate film have also been attracting attention in recent years, such as liquid crystal display elements, solar cells, electromagnetic wave shields, touch panels, EL substrates, and color filters.

[0003] Regarding such gas barrier laminate films having an inorganic layer, various improvements have been investigated. For example, from the viewpoint of providing transparency and gas barrier properties as well as boiling resistance and retort resistance without the occurrence of delamination, etc., a vapor deposition film has been disclosed in which a primer layer made of a composite of a functional group-containing silane coupling agent or a hydrolyzate of a silane coupling agent with a polyol and an isocyanate compound, and an inorganic oxide thin film layer having a thickness of 5 to 300 nm are sequentially laminated on at least one side of a plastic substrate (Patent Document 1).

[0004] In addition, from the viewpoint of excellent gas barrier properties and adhesion strength between the constituent layers, an extremely thin gas barrier laminate film has been disclosed that consists of a base film / inorganic thin film layer / anchor layer / inorganic thin film layer, in which the thickness of the anchor layer is 0.1 to 10 nm (Patent Document 2).

[0005] Furthermore, a gas barrier laminate film has been disclosed in which a barrier film is formed by laminating a silicon oxide film (SiOx) as a barrier layer on one or both sides of a plastic substrate, the barrier layer being composed of at least two silicon oxide films, the thickness of each silicon oxide film being 10 nm or more and 50 nm or less, the thickness of the barrier layer composed of two or more silicon oxide films being 20 nm or more and 200 nm or less, and the proportion of carbon atoms in the barrier layer being 10 at.% or less (Patent Document 3).

[0006] On the other hand, various proposals have been made to improve the gas barrier properties of polylactic acid films, which are biodegradable films. For example, it has been disclosed that adjusting the ratio between crystalline and amorphous regions of a polylactic acid film achieves both adhesion and gas barrier properties (Patent Document 4).

[0007] It has also been disclosed that a combination of gas barrier properties and transparency can be achieved by setting the planar orientation and heat of crystal fusion of a polylactic acid film within specific ranges (Patent Document 5).

[0008] Furthermore, a gas barrier film that has good interlayer adhesion achieved by providing an anchor layer containing a silane coupling agent on a polylactic acid film has been disclosed (Patent Document 6). [Prior art documents] [Patent documents]

[0009] [Patent Document 1] JP 2000-238172 A [Patent Document 2] International Publication No. 2007-034773 Brochure [Patent Document 3] JP 2009-101548 A [Patent Document 4] Patent No. 4452574 [Patent Document 5] JP 2006-69218 A [Patent Document 6] JP 2013-233658 A Summary of the Invention [Problem to be solved by the invention]

[0010] As described above, various studies have been conducted on gas barrier laminate films having an inorganic layer in order to improve the gas barrier properties. However, it has been found that the gas barrier properties of the films are degraded when heat is applied during the film manufacturing process. This tendency is particularly pronounced when a film with poor heat resistance, such as a polylactic acid film or a polyolefin film, is used as the base film, and the problem of the gas barrier properties being degraded when heat is applied is prominent.

[0011] The object of the present invention is to provide a new laminated film roll which, in turn, has an anchor layer and an inorganic layer on at least one side of a base film, and which can prevent a decrease in gas barrier properties and has good adhesion (lamination strength) even when a film with poor heat resistance, such as a polylactic acid film, is used as the base film, and a film laminate roll using the same. [Means for solving the problem]

[0012] The present invention relates to a laminated film having a structure in which an anchor layer and an inorganic layer are sequentially laminated on at least one surface of a base film (1), and the average linear expansion coefficient at 105 to 120°C in the longitudinal direction is -7×10 -4 ~0 / ℃ and -1×10 -3 We propose a laminated film roll with a temperature of ~0 / ℃.

[0013] The present invention also proposes a film laminate roll having a configuration in which the laminate film constituting the laminate film roll and a base film (2) are laminated together via an adhesive. Effect of the Invention

[0014] The laminated film roll proposed by the present invention has a feature that the amount of film deformation during heat treatment is small in a configuration in which an anchor layer and an inorganic layer are sequentially laminated on a substrate film. Therefore, even if a substrate film with poor heat resistance is used, it is possible to prevent the occurrence of cracks in the inorganic layer during heat treatment, and the desired gas barrier properties can be obtained. Therefore, the laminated film roll proposed by the present invention and the film laminate roll using the same can be widely used, for example, as a packaging material for preventing deterioration of foods, industrial products, medicines, etc., for packaging items that require blocking various gases such as water vapor and oxygen. In addition to packaging applications, the laminated film roll can be suitably used for various members such as liquid crystal display elements, solar cells, electromagnetic wave shields, touch panels, EL substrates, and color filters. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Next, the present invention will be described based on an embodiment, however, the present invention is not limited to the embodiment described below.

[0016] <<This laminated film roll>> A laminated film roll according to one embodiment of the present invention (referred to as "the present laminated film roll") is a laminated film roll having a configuration in which an anchor layer and an inorganic layer are laminated in this order on at least one side of a base film (referred to as "the present base film").

[0017] The laminated film roll of the present invention is a roll of a long film, but a laminated film obtained by cutting the roll into an appropriate size is similar to the laminated film roll of the present invention described below. Therefore, the laminated film roll of the present invention in the following description can be replaced with the laminated film.

[0018] <Average linear expansion coefficient> The laminated film roll of the present invention is configured by sequentially laminating an anchor layer and an inorganic layer on at least one side of the present base film, and in order to achieve both gas barrier properties and adhesion, the amount of film deformation during heat treatment is reduced. For this purpose, the dimensional change of the film in the processing temperature atmosphere when the anchor layer and the inorganic layer are provided on the present base film is suppressed. Furthermore, the present invention divides the measurement temperature of thermomechanical analysis (TMA) into three ranges, condition 1 to condition 3, and satisfies condition 1 as an essential requirement. In addition, it is preferable to satisfy condition 2 and / or condition 3, and it is most preferable to simultaneously satisfy conditions 1 to 3.

[0019] Condition 1: The average linear expansion coefficient from 105 to 120 °C in thermomechanical analysis (TMA) is -7 × 10 -4 ~0 / ℃ and -1×10 in the width direction -3 ~0 / ℃. Preferably, -6×10 -4 ~0 / ℃ and -1×10 in the width direction -3 ~0 / ℃.

[0020] Condition 2: In addition to satisfying condition 1, the average linear expansion coefficient at 90 to 105 °C in thermomechanical analysis (TMA) is multiplied by 10 in the longitudinal direction. -4 ~0 / ℃ and -3×10 in the width direction -4 It is preferable to set the temperature to -0 / ℃. Among them, the temperature is -5×10 -4 ~0 / ℃ and -5×10 in the width direction -5 It is more preferable to set the temperature to 0°C.

[0021] Condition 3: In addition to satisfying Condition 1 and / or Condition 2, the average linear expansion coefficient at 75 to 90 °C in the longitudinal direction in thermomechanical analysis (TMA) is -2 × 10 -4 ~0 / ℃, and 0~2×10 -4 / °C. In particular, the longitudinal direction is -1×10 -4 ~0 / ℃, and 0~2×10 -4 / °C is more preferable.

[0022] As a specific means for adjusting the average linear expansion coefficient in each temperature range in thermomechanical analysis (TMA) in the present laminated film roll to the above range, for example, it is preferable to adjust the average linear expansion coefficient in each temperature range of the present base film constituting the present laminated film roll. For this purpose, as a manufacturing condition of the present base film, particularly the polylactic acid film, a method of stretching under relatively low conditions, for example, a stretching ratio in the longitudinal direction and width direction is 3.0 times or less, and the stretching ratio in the transverse direction is greater than the stretching ratio in the longitudinal direction, and further a method of heat treatment at a high temperature, for example, a heat treatment at a temperature exceeding 100°C, can be exemplified. However, the present invention is not limited to this method.

[0023] <Main base film> The present base film constituting the present laminated film roll is not limited in material and configuration as long as it is a film having transparency and necessary and sufficient rigidity.

[0024] The substrate film may have a single layer structure or a multilayer structure. When the present substrate film has a multi-layer structure, it may have a two-layer or three-layer structure, or may have four or more layers.

[0025] The poorer the heat resistance of the present base film, the greater the effects of the present invention. From this viewpoint, the present base film preferably has a glass transition temperature (Tg) of 55 to 65°C, more preferably 58°C or higher or 65°C or lower, and even more preferably 60°C or higher or 65°C or lower.

[0026] From the same viewpoint as above, the present substrate film is preferably, for example, a polylactic acid film or a polyolefin film, but is not limited thereto. In the present invention, the term "polylactic acid film" or "polyolefin film" refers to a film having a layer containing polylactic acid resin or polyolefin resin as a main component resin, whether the film has a single-layer structure or a multi-layer structure. Preferably, the film has a layer containing polylactic acid resin or polyolefin resin as a main component resin as a main layer. Among these, it is preferable that the main component resin of each layer of the present substrate film is a polylactic acid resin or a polyolefin resin, whether the present substrate film has a single layer structure or a multilayer structure.

[0027] In this case, the "main layer" refers to the layer in question in the case of a single-layer film, and to the layer having the greatest thickness ratio among the layers constituting the film in the case of a multi-layer film. Further, "main component resin" means the resin that is contained in the largest proportion among the resins constituting each layer, for example, a resin that accounts for 50% by mass or more, particularly 70% by mass or more, and even more particularly 80% by mass or more (including 100% by mass) of the resins constituting each layer.

[0028] The polylactic acid film or polyolefin film may contain a resin other than the polylactic acid resin or polyolefin resin or a component other than a resin, so long as it has a layer containing a polylactic acid resin or a polyolefin resin as a main resin component.

[0029] (Polylactic acid resin) The polylactic acid resin is a homopolymer of D-lactic acid or L-lactic acid, or a copolymer thereof. That is, the polylactic acid resin may be any one of poly(D-lactic acid) whose structural unit is D-lactic acid, poly(L-lactic acid) whose structural unit is L-lactic acid, and poly(DL-lactic acid) which is a copolymer of L-lactic acid and D-lactic acid, or a mixed resin thereof. It may also be a mixed resin of a plurality of the above copolymers having different copolymerization ratios of D-lactic acid and L-lactic acid.

[0030] The copolymer of L-lactic acid and D-lactic acid has a copolymerization ratio of D-lactic acid to L-lactic acid (hereinafter abbreviated as "D / L ratio") of preferably "3 / 97" to "15 / 85" or "85 / 15" to "97 / 3", more preferably "5 / 95" to "15 / 85" or "85 / 15" to "95 / 5", even more preferably "8 / 92" to "15 / 85" or "85 / 15" to "92 / 8", and particularly preferably "10 / 90" to "15 / 85" or "85 / 15" to "90 / 10".

[0031] It is also possible to blend polylactic acids (also called "PLA") with different D / L ratios, which is more preferable since it is easier to adjust the D / L ratio of the polylactic acid resin. In this case, the average D / L ratio of the multiple lactic acid polymers should be within the above range. By blending two or more polylactic acid resins with different D / L ratios and adjusting the crystallinity according to the intended use, it is possible to achieve a balance between heat resistance and heat shrinkage properties.

[0032] The polylactic acid resin may be copolymerized with a small amount of a copolymerization component within a range that does not impair the essential properties of the PLA. Examples of the copolymerization component include at least one selected from the group consisting of α-hydroxycarboxylic acids other than lactic acid, non-aliphatic dicarboxylic acids such as terephthalic acid, aliphatic dicarboxylic acids such as succinic acid, non-aliphatic diols such as ethylene oxide adducts of bisphenol A, and aliphatic diols such as ethylene glycol.

[0033] Examples of the α-hydroxycarboxylic acid unit other than lactic acid include bifunctional aliphatic hydroxycarboxylic acids such as glycolic acid, 3-hydroxybutyric acid, 4-hydroxybutyric acid, 2-hydroxy-n-butyric acid, 2-hydroxy-3,3-dimethylbutyric acid, 2-hydroxy-3-methylbutyric acid, 2-methyllactic acid, and 2-hydroxycaproic acid, and lactones such as caprolactone, butyrolactone, and valerolactone.

[0034] Examples of the diol unit include ethylene glycol, 1,4-butanediol, 1,4-cyclohexanedimethanol, etc. Examples of the dicarboxylic acid unit include succinic acid, adipic acid, suberic acid, sebacic acid, and dodecanedioic acid, etc.

[0035] The copolymerization ratio of lactic acid and α-hydroxycarboxylic acid other than lactic acid is not particularly limited. In particular, the higher the ratio of lactic acid, the less petroleum resources are consumed, which is preferable, and it is also preferable to copolymerize at a ratio that does not exceed the range of the Vicat softening point described later. Specifically, the copolymerization ratio of a copolymer of lactic acid with an α-hydroxycarboxylic acid other than lactic acid, an aliphatic diol, or an aliphatic dicarboxylic acid, i.e., lactic acid / α-hydroxycarboxylic acid other than lactic acid, an aliphatic diol, or an aliphatic dicarboxylic acid, is from 95 / 5 to 10 / 90, preferably from 90 / 10 to 20 / 80, and more preferably from 80 / 20 to 30 / 70. If the copolymerization ratio is within the above range, a film having a good balance of physical properties such as rigidity, transparency, and impact resistance can be obtained. The copolymer may be a copolymer, a block copolymer, or a graft copolymer, and any of these structures may be used, although from the viewpoints of impact resistance and transparency of the film, block copolymers and graft copolymers are preferred.

[0036] The polylactic acid resin may also contain a small amount of a chain extender, such as a diisocyanate compound, an epoxy compound, or an acid anhydride, for the purpose of increasing the molecular weight.

[0037] The mass average molecular weight of the polylactic acid resin is 20,000 or more, preferably 40,000 or more, more preferably 60,000 or more, and the upper limit is 400,000 or less, preferably 350,000 or less, more preferably 300,000 or less. If the mass average molecular weight of the polylactic acid resin is 20,000 or more, a moderate resin cohesive force is obtained, and the film strength and elongation are insufficient or embrittlement can be suppressed. On the other hand, if the mass average molecular weight is 400,000 or less, the melt viscosity can be reduced, which is preferable from the viewpoint of improving production and productivity.

[0038] As the polymerization method of the polylactic acid resin, known methods such as condensation polymerization and ring-opening polymerization can be adopted. For example, in the case of condensation polymerization, D-lactic acid, L-lactic acid, or a mixture thereof can be directly dehydrated and condensed to obtain a polylactic acid resin having an arbitrary composition. In the case of ring-opening polymerization, lactide, which is a cyclic dimer of lactic acid, can be ring-opened and polymerized in the presence of a predetermined catalyst while using a polymerization regulator as necessary to obtain a polylactic acid resin having an arbitrary composition. The lactide includes DL-lactide, which is a dimer of L-lactic acid, and these can be mixed and polymerized as necessary to obtain a polylactic acid resin having an arbitrary composition and crystallinity.

[0039] A representative example of polylactic acid resin is commercially available "Nature Works" manufactured by Nature Works LLC. A specific example of a random copolymer of PLA, diol, and dicarboxylic acid is "GS-Pla" (manufactured by Mitsubishi Chemical Corporation), and a specific example of a block copolymer is "Plamate" (manufactured by DIC Corporation).

[0040] (Polyolefin resin) Examples of the polyolefin resin include polyethylene resin, polypropylene resin, ethylene-vinyl acetate copolymer, ethylene-ethyl acrylate copolymer, ethylene-methyl acrylate copolymer, etc. Among them, from the viewpoint of heat shrinkage rate and moldability, it is preferable to use polyethylene resin, polypropylene resin, or a mixture thereof.

[0041] As a polyethylene resin, it has a density of 0.92 g / cm 3 More than 0.94g / cm 3 Medium density polyethylene resin (MDPE) with a density of 0.92 g / cm 3Examples of suitable low density polyethylene resins include low density polyethylene resins (LDPE) having a density of less than 1000 nm and linear low density polyethylene resins (LLDPE). Among these, linear low density polyethylene resins (LLDPE) are preferably used from the viewpoints of stretchability, impact resistance of the film, transparency, etc.

[0042] The linear low density polyethylene resin (LLDPE) may be a copolymer of ethylene and an α-olefin having 3 to 20 carbon atoms, preferably 4 to 12 carbon atoms. Examples of the α-olefin include propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 3-methyl-1-butene, and 4-methyl-1-pentene. Among these, 1-butene, 1-hexene, and 1-octene are preferably used. The α-olefin to be copolymerized may be used alone or in combination of two or more.

[0043] The polyolefin resin contains a polyethylene component, and the content thereof is preferably 70% by mass or more, and more preferably 75% by mass or more. If the content is 70% by mass or more, the strength of the entire film can be maintained.

[0044] In particular, the density of polyethylene resin is 0.910 g / cm 3 It is preferable that the density is 0.905 g / cm or less. 3 Less than 0.900 g / cm is more preferable. 3 The lower limit is preferably 0.800 g / cm or less. 3 More than 0.850 g / cm is preferable. 3 More preferably, 0.880 g / cm 3 More preferably, the density is 0.910 g / cm 3 If the density is less than 0.800 g / cm, the affinity with polylactic acid is improved, and the stretchability is maintained, so that a sufficient heat shrinkage rate can be obtained in the practical temperature range (70°C to 90°C). 3 If the thickness is more than this, the stiffness (rigidity at room temperature) and heat resistance of the entire film are not significantly decreased, which is preferable from a practical standpoint.

[0045] The polyethylene resin preferably has a melt flow rate (MFR: JIS K 7210, temperature: 190° C., load: 21.18 N) of 0.1 g / 10 min or more and 10 g / 10 min or less. If the MFR is 0.1 g / 10 min or more, good extrusion processability can be maintained, while if the MFR is 10 g / 10 min or less, thickness unevenness of the laminated film roll and reduction in mechanical strength are unlikely to occur, which is preferable.

[0046] The polypropylene resin may be a homopropylene resin or a soft polypropylene resin having greater flexibility than the homopropylene resin. Examples of the soft polypropylene resin include random polypropylene resin, block polypropylene resin, and propylene-ethylene rubber. Among these, random polypropylene resin is particularly preferably used from the viewpoint of stretchability and breakage resistance.

[0047] In the random polypropylene resin, the α-olefin to be copolymerized with propylene preferably has 2 to 20 carbon atoms, more preferably 4 to 12 carbon atoms, and examples thereof include ethylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, and 1-decene. Among them, a random polypropylene having a propylene unit content of 80% by mass or more, preferably 85% by mass or more, more preferably 90% by mass or more as an α-olefin is particularly preferably used from the viewpoints of stretchability, heat shrinkage properties, impact resistance, transparency, rigidity, etc. of the film. Moreover, the α-olefin to be copolymerized may be used alone or in combination of two or more kinds.

[0048] The melt flow rate (MFR) of the polypropylene resin is usually 0.5 g / 10 min or more, preferably 1.0 g / 10 min or more, and 15 g / 10 min or less, preferably 10 g / 10 min or less, in terms of MFR (JIS K 7210, temperature: 230° C., load: 21.18 N).

[0049] Specific examples of commercially available products include polyethylene resins under the trade names "Novatec LD, LL," "Kernel," and "Tafmer A, P" (manufactured by Nippon Polyethylene Co., Ltd.), "Suntech HD, LD" (manufactured by Asahi Kasei Chemicals Corporation), "HIZEX," "ULTZEX," and "EVOLUE" (manufactured by Mitsui Chemicals, Inc.), "Moatec" (manufactured by Idemitsu Kosan Co., Ltd.), "UBE Polyethylene" and "UMERIT" (manufactured by Ube Industries, Ltd.), "NUC Polyethylene" and "Nacflex" (manufactured by Nippon Unicar Co., Ltd.), and "Engage" (manufactured by The Dow Chemical Company).

[0050] Polypropylene resins are commercially available under the product names "Novatec PP," "WINTEC," and "Tafmer XR" (manufactured by Japan Polypropylene Corporation), "Mitsui Polypro" (manufactured by Mitsui Chemicals), "Sumitomo Noblen," "Tafthren," and "Excellen EPX" (manufactured by Sumitomo Chemical Co., Ltd.), "IDEMITSU PP," and "IDEMITSU TPO" (manufactured by Idemitsu Kosan Co., Ltd.), "Adflex," "Adsyl" (manufactured by Sunallomer Corporation), and "VERSIFY" (manufactured by The Dow Chemical Company).

[0051] As the polyolefin resin, a copolymer of the ethylene and a monomer copolymerizable therewith can also be suitably used. Examples of the copolymer of the ethylene and a monomer copolymerizable therewith include an ethylene-vinyl acetate copolymer, an ethylene-ethyl acrylate copolymer, and an ethylene-methyl acrylate copolymer.

[0052] The ethylene content of the ethylene-vinyl acetate copolymer, ethylene-ethyl acrylate copolymer, and ethylene-methyl acrylate copolymer is desirably 70% by mass or more, preferably 75% by mass or more, and 95% by mass or less, preferably 90% by mass or less, and more preferably 85% by mass or less. If the ethylene content is 70% by mass or more, the break resistance and shrinkage properties of the entire film can be maintained well.

[0053] Commercially available ethylene-vinyl acetate copolymers (EVA) include, for example, "Evaflex" (manufactured by DuPont-Mitsui Polychemicals), "Novatec EVA" (manufactured by Mitsubishi Chemical), "Evaslen" (manufactured by DIC), and "Evatate" (manufactured by Sumitomo Chemical). Commercially available ethylene / ethyl acrylate copolymers (EEA) include, for example, "Evaflex EEA" (manufactured by DuPont-Mitsui Polychemicals), and ethylene / methyl acrylate copolymers include, for example, "Elbaloy AC" (manufactured by DuPont-Mitsui Polychemicals).

[0054] The MFR of the copolymer of ethylene and a copolymerizable monomer is not particularly limited. Usually, the MFR (JIS K 7210, temperature: 190°C, load: 21.18N) is preferably 0.5g / 10min or more at the lower limit, more preferably 1.0g / 10min or more at the upper limit, and is preferably 15g / 10min or less, more preferably 10g / 10min or less at the upper limit.

[0055] The polyolefin resin has a mass average molecular weight of preferably 50,000 or more, more preferably 100,000 or more, and an upper limit of 700,000 or less, more preferably 600,000 or less, and even more preferably 500,000 or less. If the mass average molecular weight of the polyolefin resin is within the above range, it can exhibit the desired practical physical properties such as mechanical properties and heat resistance, and can obtain an appropriate melt viscosity and good moldability.

[0056] The method for producing the polyolefin resin is not particularly limited, and examples thereof include known polymerization methods using known olefin polymerization catalysts, such as a slurry polymerization method, a solution polymerization method, a bulk polymerization method, and a gas phase polymerization method using a multi-site catalyst represented by a Ziegler-Natta type catalyst or a single-site catalyst represented by a metallocene catalyst, and a bulk polymerization method using a radical initiator.

[0057] (particle) The present substrate film may contain particles for the main purposes of roughening the film surface to impart slipperiness and preventing the occurrence of scratches in each process. The type of the particles is not particularly limited as long as they are particles that can provide easy slipping. For example, inorganic particles such as silica calcium carbonate, magnesium carbonate, barium carbonate, calcium sulfate, calcium phosphate, magnesium phosphate, kaolin, aluminum oxide, and titanium oxide, and organic particles such as acrylic resin, styrene resin, urea resin, phenol resin, epoxy resin, and benzoguanamine resin can be mentioned. These can be used alone or in combination of two or more of them. The shape of the particles is not particularly limited, and may be, for example, spherical, blocky, rod-like, flat, or the like. Furthermore, there is no particular limitation on the hardness, specific gravity, color, etc. of the above particles. Two or more kinds of these particles may be used in combination as necessary.

[0058] The average particle size of the particles is preferably 5.0 μm or less, more preferably 0.01 μm or more or 3.0 μm or less, and even more preferably 0.5 μm or more or 2.5 μm or less. If the average particle size of the particles is 5 μm or less, the surface roughness of the present base film does not become too rough, and in that respect, problems when forming an anchor layer or an inorganic layer on the surface of the present base film can be reduced.

[0059] The particle content is preferably 5% by mass or less of the present substrate film, more preferably 0.0003% by mass or more or 3% by mass or less, and even more preferably 0.01% by mass or more or 2% by mass or less. By setting the particle content in the above range, it is possible to achieve both the slipperiness and transparency of the film, which is preferable.

[0060] The method for adding particles to the substrate film is not particularly limited, and any conventionally known method can be used.

[0061] (Other ingredients) The present substrate film may contain, as necessary, conventionally known antioxidants, antistatic agents, heat stabilizers, lubricants, dyes, pigments, ultraviolet absorbers, and the like.

[0062] (Base film thickness) The thickness of the present substrate film is not particularly limited as long as it is within a range that allows the substrate film to be formed into a film, and is preferably 9 μm to 100 μm, more preferably 12 μm or more or 75 μm or less, and even more preferably 15 μm or more or 60 μm or less.

[0063] The present substrate film can be formed, for example, by forming the resin composition into a film shape by a melt casting method or a solution casting method. In the case of a multi-layer structure, co-extrusion may be used. The film may be uniaxially or biaxially stretched, and is preferably a biaxially stretched film from the viewpoint of rigidity.

[0064] (characteristic) From the viewpoint of adjusting the average linear expansion coefficient within a predetermined temperature range for the present laminated film roll as described above, the measurement temperature for analysis (TMA) for the present base film is divided into three ranges, Condition 2-1 to Condition 2-3, and it is preferable that Condition 2-1 is satisfied, and in addition, Condition 2-2 and / or Condition 2-3 are satisfied, and it is most preferable that Conditions 2-1 to 2-3 are satisfied simultaneously. It should be noted that conditions 1, 2, and 3 of the present laminated film roll correspond to conditions 2-1, 2-2, and 2-3 of the present base film, respectively.

[0065] Condition 2-1: The average linear expansion coefficient from 105 to 120 °C in thermomechanical analysis (TMA) is -1 × 10 -3 ~0 / ℃ and -9×10 in the width direction -3 0 / ℃, and in particular, −7×10 -4 ~0 / ℃ and -1×10 in the width direction -3 It is more preferable to set the temperature to 0°C.

[0066] Condition 2-2: In addition to satisfying condition 2-1, the average linear expansion coefficient at 90 to 105 °C in the longitudinal direction in thermomechanical analysis (TMA) is -7 × 10 -4 ~0 / ℃ and -5×10 in the width direction -4It is preferable to set the temperature to 0°C or less, and in particular, to -5×10 -4 ~0 / ℃ and -3×10 in the width direction -4 It is more preferable to set the temperature to 0°C.

[0067] Condition 2-3: In addition to satisfying Condition 2-1 and / or Condition 2-2, the average linear expansion coefficient at 75 to 90 °C in the longitudinal direction in thermomechanical analysis (TMA) is -5 × 10 -4 ~0 / ℃, and 0~6×10 -4 / °C, and in particular, the longitudinal direction is -2×10 -4 ~0 / ℃, and 0~2×10 -4 / °C is more preferable.

[0068] As a specific means for controlling the average linear expansion coefficient in each temperature range in thermomechanical analysis (TMA) of the present base film to the above range, for example, the production conditions of the present base film, particularly the polylactic acid film, may include a method in which the stretching is performed under relatively low conditions, for example, the stretching ratios in the longitudinal and width directions are 3.0 times or less and the stretching ratio in the transverse direction is greater than the stretching ratio in the longitudinal direction, and further, heat treatment is performed at a high temperature, for example, heat treatment at a temperature exceeding 100° C. However, the method is not limited to this method.

[0069] (Production method) An example of a method for producing the substrate film will be described below.

[0070] First, using a known method, raw materials, such as polylactic acid raw materials, are supplied to a melt extrusion device and heated to above the melting point of each polymer. The molten polymer is extruded through a die and cooled to a temperature below the glass transition point of the polymer on a rotating cooling drum to solidify the polymer, thereby obtaining an unoriented sheet in a substantially amorphous state. Next, the unoriented sheet is stretched in one direction, usually the longitudinal direction, by a roll or tenter type stretching machine, at a stretching temperature of usually 25 to 120° C., preferably 35 to 100° C., and at a stretching ratio of usually 2.5 to 5.0 times, preferably 2.8 to 4.0 times.

[0071] Then, the film is stretched in a direction perpendicular to the first stretching direction, usually in the width direction, at a stretching temperature of usually 50 to 140° C. and a stretch ratio of usually 2.6 to 5.0 times, preferably 2.6 to 4.0 times.

[0072] In order to set the average linear expansion coefficient in each temperature range in thermomechanical analysis (TMA) within the above range, it is preferable that the stretch ratios in the longitudinal direction and width direction are 3.0 times or less and the stretch ratio in the transverse direction is greater than the stretch ratio in the longitudinal direction, as described above.

[0073] Then, the film is subsequently heat-set at a temperature of 100 to 160° C. under tension or under relaxation of 20% or less, to obtain the present substrate film as a biaxially oriented film. In order to set the average linear expansion coefficient in each temperature range in thermomechanical analysis (TMA) to the above range, it is preferable to carry out the heat treatment at a temperature exceeding 100° C., as described above. In the above-mentioned stretching, a method in which the stretching in one direction is carried out in two or more stages can also be adopted.

[0074] <Main anchor layer> The anchor layer (hereinafter referred to as "the anchor layer") constituting the present laminated film roll is a layer having a function of enhancing the adhesion between the present substrate film and the present inorganic layer.

[0075] The anchor layer can usually be formed from an anchor coating agent. The main component resin of the anchor layer or the anchor coating agent may be a solvent-based or water-based polyester, a urethane resin, an acrylic resin, a vinyl alcohol resin, an ethylene vinyl alcohol resin, a vinyl modified resin, an oxazoline group-containing resin, a carbodiimide group-containing resin, an epoxy group-containing resin, an isocyanate group-containing resin, an alkoxyl group-containing resin, a modified styrene resin, and a modified silicone resin, and these may be used alone or in combination of two or more. Among them, from the viewpoint of adhesion and hot water resistance, it is preferable to use at least one selected from polyester, urethane resin, acrylic resin, oxazoline group-containing resin, carbodiimide group-containing resin, epoxy group-containing resin, isocyanate-containing resin, and copolymers thereof alone or in combination of two or more. Among them, at least one resin selected from the group consisting of polyester, urethane resin, and acrylic resin is preferable.

[0076] In addition, it is preferable that the main component resin of the anchor layer or the anchor coating agent accounts for 40 mass % or more of the resin constituting the anchor layer or the anchor coating agent, preferably 50 mass % or more, more preferably 60 mass % or more, more preferably 70 mass % or more, and more preferably 90 mass % or more (including 100 mass %).

[0077] The anchor layer preferably further contains a cured product obtained by curing a curable resin. The curable resin may be a photocurable resin or a thermosetting resin, and among them, those containing an isocyanate compound are particularly preferred. In this case, the content of the isocyanate compound in the anchor layer is preferably 1 to 50 parts by mass relative to 100 parts by mass of the main component resin, and more preferably 5 parts by mass or more or 40 parts by mass or less, and even more preferably 10 parts by mass or more or 30 parts by mass or less. Therefore, the present anchor layer is preferably a layer formed by coating the present substrate film with a resin composition containing a curable resin, and then subjecting the coated film to a curing treatment.

[0078] If the thickness of the anchor layer is 5.00 μm or less, the slip properties are good and there is almost no peeling from the base film due to internal stress of the anchor layer itself, and a thickness of 0.02 μm or more is preferable because a uniform thickness can be maintained. From this viewpoint, the thickness of the present anchor layer is preferably 0.02 to 5.00 μm, more preferably 0.03 μm or more or 3.00 μm or less, and even more preferably 0.05 μm or more or 1.00 μm or less.

[0079] The anchor layer preferably has a peak temperature of loss tangent (tan δ) in dynamic viscoelasticity measurement of 60.0° C. or higher, more preferably 70.0° C. or higher, even more preferably 80.0° C. or higher, and even more preferably 85.0° C. or higher.

[0080] In order to impart the viscoelasticity to the present anchor layer, for example, it is preferable that the present anchor layer contains a cured product obtained by curing a curable resin. Therefore, it is preferable to form the present anchor layer by coating a resin composition containing a heat- or light-curable resin on the present substrate film and curing the heat- or light-curable resin with heat or light. However, the method of imparting the viscoelasticity to the present anchor layer is not limited to this method. Among them, it is particularly preferable to select and use an isocyanate compound as the thermosetting resin.

[0081] As described above, by laminating an anchor layer having a storage modulus of 10.0 MPa or more at 120°C to a thickness of 0.02 μm or more and 5.00 μm or less as the anchor layer constituting the present laminated film roll, it is possible to obtain good barrier properties and adhesion even when an inorganic layer is provided on a base film having poor heat resistance, such as a polylactic acid (PLA) film or an oriented polypropylene (OPP) film. The mechanism by which such good barrier properties can be exhibited can be assumed as follows. In general, when an inorganic layer is vapor-deposited on a substrate film having poor heat resistance, the substrate film tends to shrink due to heat damage caused during vapor deposition. Generally, when an anchor layer is interposed between a substrate and an inorganic layer, the adhesion between the substrate film and the inorganic layer tends to be improved, and therefore the force of shrinkage of the substrate film is directly transmitted to the inorganic layer, causing cracks and the like, thereby reducing the barrier property. In contrast, in the present laminated film roll, attention is focused on the average expansion coefficient of the laminated film roll provided with a base film, an anchor layer, and an inorganic layer, and by controlling this parameter within a certain range, the force tending to shrink the base film or the laminated film roll itself is suppressed, thereby suppressing the occurrence of cracks in the inorganic layer, and it is presumed that good barrier properties capable of withstanding heat can be obtained.

[0082] <This inorganic layer> The inorganic layer constituting the present laminated film roll (hereinafter referred to as the "present inorganic layer") is a layer containing an inorganic substance, particularly an inorganic oxide, as a main material. The "main material" means a material that occupies 50% by mass or more, preferably 70% by mass or more, preferably 80% by mass or more, and preferably 90% by mass or more (including 100% by mass) of the inorganic layer.

[0083] The inorganic layer is a layer that can enhance the property of suppressing gas permeation (also called "gas barrier property"), particularly the water vapor barrier property. Furthermore, in the case of the inorganic layer, by including alkali metal ions, even higher gas barrier property can be realized.

[0084] The inorganic material serving as the main material constituting the present inorganic layer can include at least one or more inorganic compounds selected from silicon oxide, silicon nitride, silicon oxynitride, silicon oxide carbide, silicon oxycarbonitride, aluminum oxide, aluminum nitride, aluminum oxynitride, and aluminum oxide carbide.

[0085] As the inorganic layer, for example, a PVD inorganic layer formed by physical vapor deposition (PVD), a plasma-assisted deposition inorganic layer formed by plasma-assisted deposition, a CVD inorganic layer formed by chemical vapor deposition (CVD), a coated inorganic layer formed by a method of dispersing inorganic particles in an organic polymer and applying the mixture, etc. are preferably used. Here, as representative examples of the inorganic layer, the PVD inorganic layer, the plasma-assisted deposition inorganic layer, and the CVD inorganic layer will be described.

[0086] (PVD Inorganic Layer) It is preferable that the inorganic layer includes at least one PVD inorganic layer formed by physical vapor deposition (PVD) because higher gas barrier properties can be exhibited.

[0087] As an example of the PVD inorganic layer, a layer composed of silicon oxide represented by SiOx (1.0 < x ≤ 2.0) can be mentioned. At this time, if the value (lower limit value) of x in the SiOx becomes smaller, the gas permeability becomes smaller, and the gas barrier properties of the inorganic layer can be enhanced. On the other hand, the silicon oxide film itself tends to have yellowness and low transparency. From such a viewpoint, x in the SiOx is more preferably 1.2 ≤ x ≤ 2.0, and among them, 1.4 ≤ x ≤ 2.0 is even more preferable. The above composition can be confirmed by XPS analysis or the like.

[0088] The preferable pressure during the formation of the PVD inorganic layer is preferably 1×10 -7 Pa to 1 Pa from the viewpoints of gas barrier properties, vacuum evacuation ability, and the degree of oxidation of the SiOx layer to be formed, and among them, 1×10 -6 or more or 1×10 -1 Pa or less, and among them, 1×10 -4 or more or 1×10 -2 Pa or less is even more preferable. The partial pressure during the introduction of oxygen is preferably in the range of 10 to 90% with respect to the total pressure, and among them, 20% or more or 80% or less is even more preferable.

[0089] As described above, the inorganic layer preferably includes at least one PVD inorganic layer. In this case, the inorganic layer may be a single layer structure consisting of a PVD inorganic layer, or may be a multi-layer structure (two or more layers) in which a CVD inorganic layer described later or a PVD inorganic layer having the same or different composition is laminated on the PVD inorganic layer to ensure higher gas barrier properties. For example, a structure in which a PVD inorganic layer and a CVD inorganic layer are alternately formed (for example, a three-layer structure of a PVD inorganic layer, a CVD inorganic layer, and a PVD inorganic layer) can be used. In addition, by forming a CVD inorganic layer on a PVD inorganic layer, defects and the like that occur in the PVD inorganic layer are filled, and gas barrier properties and adhesion between layers tend to be improved.

[0090] (Plasma-assisted deposition inorganic layer) If the present inorganic layer is formed from a plasma-assisted deposited inorganic layer, the transparency can be improved without deteriorating the gas barrier property. The term "plasma-assisted deposition method" refers to a method in which, during vacuum deposition, the deposition material is deposited while being ionized by plasma, or by irradiating gaseous ions from a separately provided ion source. By forming the inorganic layer by plasma-assisted deposition, oxygen can be efficiently incorporated into the inorganic layer, and as described above, transparency can be improved without deteriorating the gas barrier properties. Thin films formed by normal vacuum deposition have smaller energy of flying particles than thin films formed by sputtering, and are not advantageous in terms of film strength or density. On the other hand, according to the plasma-assisted deposition method, the deposition material obtains energy, so that thin films with high strength and density can be formed even by vacuum deposition. In addition, since the excited species in the plasma are highly reactive, it is possible to form thin films by optionally oxidizing, nitriding, or carbonizing the evaporation source by introducing gases such as oxygen, nitrogen, and acetylene. By providing the inorganic layer by this method, there is also the advantage that the film can be formed more quickly than by sputtering or plasma CVD.

[0091] As an example of the plasma-assisted vapor-deposited inorganic layer, a layer composed of silicon oxide represented by SiOx (1.0 < x ≦ 2.0) can be mentioned. As described above, if oxygen gas is introduced into this inorganic layer by the plasma-assisted vapor deposition method, the oxygen molar ratio of silicon oxide can be increased. Therefore, x in the SiOx can be set to 1.2 ≦ x ≦ 2.0, and further to 1.4 ≦ x ≦ 2.0, so that the transparency can be further enhanced. Note that, generally, as the oxygen molar ratio (x) increases, the gas barrier property decreases. For this laminated film roll, an excellent gas barrier property can be maintained.

[0092] (CVD inorganic layer) When this inorganic layer includes at least one CVD inorganic layer, the CVD inorganic layer is preferably composed of a thin film formed by chemical vapor deposition of at least one selected from metals, metal oxides, metal nitrides, and silicon compounds. As the metal oxide or metal nitride, from the viewpoints of gas barrier property and adhesion, it is preferable to use oxides, nitrides of the metal, and mixtures thereof. Also, it may be a metal oxide or metal nitride obtained by plasma decomposition of an organic compound. Also, from the viewpoints of gas barrier property and adhesion, it is also preferable to use metals or compounds such as silicon and aluminum.

[0093] As a preferable example of this inorganic layer, a configuration can be mentioned which is composed of a thin film formed by chemical vapor deposition of at least one selected from silicon compounds such as silicon oxide, silicon carbon oxide, silicon oxynitride, silicon carbon oxynitride, silicon nitride, and aluminum oxide. Examples of the silicon compounds include silane, tetramethoxysilane, tetraethoxysilane, tetra-n-propoxysilane, tetraisopropoxysilane, tetra-n-butoxysilane, tetra-t-butoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, diethyldimethoxysilane, diphenyldimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, phenyltriethoxysilane, (3,3,3-trifluoropropyl)trimethoxysilane, hexafluoro ... samethyldisiloxane, bis(dimethylamino)dimethylsilane, bis(dimethylamino)methylvinylsilane, bis(ethylamino)dimethylsilane, N,O-bis(trimethylsilyl)acetamide, bis(trimethylsilyl)carbodiimide, diethylaminotrimethylsilane, dimethylaminodimethylsilane, hexamethyldisilazane, hexamethylcyclotrisilazane, heptamethyldisilazane, nonamethyltrisilazane, octamethylcyclotetrasilazane, tetrakis dimethylaminosilane, tetraisocyanatosilane, tetramethyldisilazane, tris(dimethylamino)silane, triethoxyfluorosilane, allyldimethylsilane, allyltrimethylsilane, benzyltrimethylsilane, bis(trimethylsilyl)acetylene, 1,4-bistrimethylsilyl-1,3-butadiyne, di-t-butylsilane, 1,3-disilabutane, bis(trimethylsilyl)methane, cyclopentadienyltrimethylsilane, phenyldimethylsilane, Examples of such silanes include phenyltrimethylsilane, propargyltrimethylsilane, tetramethylsilane, trimethylsilylacetylene, 1-(trimethylsilyl)-1-propyne, tris(trimethylsilyl)methane, tris(trimethylsilyl)silane, vinyltrimethylsilane, hexamethyldisilane, octamethylcyclotetrasiloxane, tetramethylcyclotetrasiloxane, hexamethyldisiloxane, hexamethylcyclotetrasiloxane, and M silicate 51.

[0094] The CVD inorganic layer preferably contains carbon, and the carbon content of the CVD inorganic layer is preferably 0.5 at.% or more, more preferably 1 at.% or more, and even more preferably 2 at.% or more. By containing a small amount of carbon in the CVD inorganic layer, stress relaxation is efficiently performed and curling of the barrier film itself can also be reduced. On the other hand, from the viewpoint of gas barrier properties, the carbon content in the CVD inorganic layer is preferably less than 20 at.%, more preferably 10 at.% or less, and most preferably 5 at.% or less. By setting the carbon content within the above range, the surface energy of the inorganic layer is increased, and the adhesion between the inorganic layers is improved, thereby improving the bending resistance and peel resistance of the barrier film. Note that "at.%" indicates the atomic composition percentage (atomic%). The composition can be confirmed by XPS analysis, etc.

[0095] The CVD inorganic layer can be formed by, for example, the method described in JP-A-2013-226829. For example, when a layer made of silicon oxide is formed by a chemical vapor deposition (CVD) method, any silicon compound can be used as a raw material in any state of gas, liquid, or solid at room temperature and pressure. In the case of a gas, it can be introduced directly into the discharge space. In the case of a liquid or solid, it is preferable to vaporize it by means of heating, bubbling, decompression, ultrasonic irradiation, or the like before use. It may also be used after dilution with a solvent. As the solvent, an organic solvent such as methanol, ethanol, or n-hexane, or a mixture of these solvents, can be used.

[0096] When carrying out the chemical vapor deposition (CVD) method, it is preferable to carry out the chemical vapor deposition (CVD) method while transporting the present substrate film, particularly the present substrate film provided with an anchor layer, at a speed of 100 m / min or more in a reduced pressure environment of 10 Pa or less. The pressure when forming a thin film by chemical vapor deposition (CVD) is preferably reduced to form a dense thin film. From the viewpoint of the film formation rate and barrier properties, the pressure is preferably 10 Pa or less, and more preferably 1×10 -2 or less than 5 Pa, among which 1×10 -1 More preferably, the pressure is 1 Pa or less.

[0097] If necessary, the CVD inorganic layer may be subjected to a crosslinking treatment by electron beam irradiation in order to improve water resistance and durability.

[0098] (Layer composition of the inorganic layer) The inorganic layer may be of a single layer construction or a multi-layer construction of two or more layers. For example, an example of a multi-layer structure having two or more layers can be one in which one layer is an inorganic layer consisting of only an inorganic material, such as an inorganic oxide, and the other layer is an inorganic-organic mixed layer consisting of an inorganic material, such as an inorganic oxide, and an organic material.

[0099] By mixing an organic material with an inorganic material to form the inorganic layer, the inorganic layer can be made relatively flexible, and the provision of such a flexible layer may improve the gas barrier properties. That is, the coarse protrusions of the base film may cause minute defects called pinholes on the surface of the inorganic layer, or the raw material may fly in clumps during heating and vapor deposition and adhere to the surface of the inorganic layer, causing minute defects. The gas may pass through the gaps caused by these defects, resulting in a decrease in gas barrier properties. Therefore, by laminating a flexible layer as described above on the surface, the defects may be filled, and the gas barrier properties may be improved. The term "flexible layer" as used herein includes the meaning of a layer that relieves stress on the inorganic layer so as to accommodate applications requiring flexibility, such as flexible applications.

[0100] As described above, in order to form a flexible layer, an organic material may be mixed with the inorganic material to form a layer. Examples of the organic material include organic materials such as polyester resin, acrylic resin, urethane resin, and PVA, as well as organic fillers.

[0101] (Thickness of inorganic layer) The thickness of the inorganic layer (the total thickness of the layers when the inorganic layer has a multi-layer structure) is preferably 0.1 nm to 500 nm, more preferably 1 nm or more or 300 nm or less, and even more preferably 5 nm or more or 100 nm or less. If the thickness of the present inorganic layer is within the above range, it is possible to ensure the desired gas barrier properties.

[0102] (Main crosslinked resin layer) The present laminate film roll may further include a crosslinked resin layer (referred to as the present crosslinked resin layer) on the present inorganic layer, if necessary.

[0103] The crosslinked resin layer may be any layer containing a crosslinked resin formed by crosslinking a resin, and is preferably a layer having a crosslinked resin as a basic skeleton.

[0104] The crosslinked resin layer is more flexible than the inorganic layer, and therefore can absorb the surface irregularities of the inorganic layer, thereby improving the gas barrier properties and suppressing yellowing or yellow-browning caused by the inorganic layer.

[0105] (Composition of the Crosslinked Resin Layer) The present crosslinked resin layer is preferably a layer having a crosslinked resin structure obtained by crosslinking and curing a crosslinkable resin composition containing a binder resin as a main component resin and other components such as a curing agent or a crosslinking initiator. In this case, the "main component resin" refers to the resin that has the largest content (mass%) among the resins that make up the present crosslinked resin layer, and can be 50 mass% or more of the resin that makes up the present crosslinked resin layer, particularly 70 mass% or more, particularly 80 mass% or more, and particularly 90 mass% or more (including 100 mass%).

[0106] (binder resin) Examples of the binder resin include water-soluble epoxy resins, water-dispersible polyurethane resins, and water-dispersible urethane acrylates, which will be described below.

[0107] [Water-soluble epoxy resin] As the water-soluble epoxy resin, it is preferable to use a water-soluble epoxy resin which is a prepolymer having an epoxy group at the terminal. Among them, those in which the prepolymer chain is aromatic are preferred.Specific examples include epoxy resins having a glycidylamine moiety derived from metaxylylenediamine, epoxy resins having a glycidylamine moiety derived from 1,3-bis(aminomethyl)cyclohexane, epoxy resins having a glycidylamine moiety derived from diaminodiphenylmethane, epoxy resins having a glycidylamine moiety and / or a glycidyl ether moiety derived from paraaminophenol, epoxy resins having a glycidyl ether moiety derived from bisphenol A, epoxy resins having a glycidyl ether moiety derived from bisphenol F, epoxy resins having a glycidyl ether moiety derived from phenol novolac, and epoxy resins having a glycidyl ether moiety derived from resorcinol.Among these, epoxy resins having a glycidylamine moiety derived from metaxylylenediamine are particularly preferred.

[0108] [Water-dispersible polyurethane resin] The water-dispersible polyurethane resin may be, but is not limited to, a polyurethane resin obtained by reacting a polyol compound not containing a carboxyl group in the molecule with a polyisocyanate compound, and forcibly emulsifying the polyurethane compound in water using a surfactant.

[0109] [Water-dispersible urethane acrylate] The water-dispersed urethane acrylate may be, for example, a water-dispersed urethane acrylate obtained by mixing a urethane acrylate raw material with an emulsifier, for example, an anionic and / or nonionic reactive emulsifier, and an oil-soluble polymerization initiator, and then subjecting the mixture to emulsion polymerization in a manner that disperses the mixture while subjecting it to heat treatment using an emulsifier, for example, a homomixer or an ultrasonic disperser, etc. However, the water-dispersed urethane acrylate is not limited thereto.

[0110] As the urethane acrylate raw material, a radical polymerizable oligomer having two or more acryloyl groups or methacryloyl groups in one molecule can be used. Examples of commercially available urethane acrylates include Beamset 505A-6 (manufactured by Arakawa Chemical Industries, Ltd.), Ebecryl 270 (manufactured by Daicel Industries, Ltd.), UA-160TM, UA-7100, (Shin-Nakamura Chemical Co., Ltd.), and the like.

[0111] The emulsifier is not particularly limited as long as it is an emulsifier that can be used in emulsion polymerization. Examples of the anionic reactive emulsifier include commercially available products such as the Aqualon series: KH-05, KH-10, AR-10, and AR-20 (trade names: manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), Antox-MS-60 and Antox-MS-2N (manufactured by Nippon Nyukazai Co., Ltd.), and the Adeka Reasoap series: SE-10N, SE-20N, and SR-10 (manufactured by Adeka Co., Ltd.). Among these, those made of sulfonate salts are preferred. Examples of the nonionic reactive emulsifiers include commercially available products such as the Adeka Reasoap series: NE-10, NE-20, NE-30, ER-10, ER-20, ER-30, and ER-40 (manufactured by Adeka), and the Latemul series: PD-420, PD-430, and PD-450 (manufactured by Kao).

[0112] Examples of the oil-soluble polymerization initiator include 2,2'-azobisisobutyronitrile, 2,2'-azobis-(2-methylpropanenitrile), 2,2'-azobis-(2,4-dimethylpentanenitrile), 2,2'-azobis-(2-methylbutanenitrile), 1,1'-azobis-(cyclohexanecarbonitrile), 2,2'-azobis-(2,4-dimethyl-4-methoxyvaleronitrile), 2,2'-azobis-(2,4-dimethylvaleronitrile), and the like. Examples of the initiator include azo(azobisnitrile) type initiators such as 2,2'-azobis-(2-amidinopropane) hydrochloride, and peroxide type initiators such as benzoyl peroxide, cumene hydroperoxide, hydrogen peroxide, acetyl peroxide, lauroyl peroxide, persulfates (e.g., ammonium persulfate), and peracid esters (e.g., t-butyl peroctate, α-cumyl peroxypivalate, and t-butyl peroctate).

[0113] (Curing agent or crosslinking initiator) It is preferable to use a curing agent or a crosslinking initiator appropriately depending on whether a crosslinking method, thermal crosslinking or photocrosslinking, is selected and further depending on what is used as the binder resin. For example, when a water-soluble epoxy resin is used as the binder resin, it is preferable to use an amine compound as the curing agent, and among these, aromatic amines such as metaphenylenediamine, diaminodiphenylmethane, and diaminodiphenylsulfone are preferable.

[0114] When the crosslinkable resin composition is to be photocrosslinked, it is preferable to add a photopolymerization initiator. The photopolymerization initiator is not particularly limited, and examples thereof include ketone-based photopolymerization initiators and amine-based photopolymerization initiators.

[0115] (solvent) As the aqueous solvent, water or an alcohol solvent can be used as the main solvent. Specific examples of the alcohol solvent include, but are not limited to, methanol, ethanol, isopropyl alcohol, and butanol.

[0116] (Other ingredients) The crosslinked resin layer may contain other components or materials in addition to the materials mentioned above. The "other components or materials" may include inorganic fillers, oxygen scavengers, coupling agents, curing accelerators, and the like.

[0117] The inorganic filler may contain inorganic fillers such as silica, alumina, mica, talc, aluminum flakes, glass flakes, etc., in order to improve the performance of the crosslinked resin layer, such as gas barrier properties, impact resistance, heat resistance, etc. In addition, when the transparency of the top coat layer is taken into consideration, it is preferable that the inorganic filler is flat.

[0118] The oxygen scavenger may be any compound having an oxygen scavenging function, such as hindered phenols, vitamin C, vitamin E, organic phosphorus compounds, gallic acid, pyrogallol, and other low molecular weight organic compounds that react with oxygen, and transition metal compounds such as cobalt, manganese, nickel, iron, and copper.

[0119] The above coupling agent may be contained in the present crosslinked resin layer, if necessary, from the viewpoint of improving the adhesion between the present crosslinked resin layer and the present inorganic layer or improving the gas barrier property. As the coupling agent, a silane coupling agent or a titanium coupling agent may be added. As the coupling agent, commercially available products can be used. Specifically, amino-based silane coupling agents such as N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, and N,N'-bis[3-trimethoxysilyl]propyl]ethylenediamine, available from Chisso Corporation, Dow Corning Toray Co., Ltd., Shin-Etsu Chemical Co., Ltd., etc., 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane can be used. Examples of suitable silane coupling agents include epoxy-based silane coupling agents such as 3-glycidoxypropyltriethoxysilane, methacryloxy-based silane coupling agents such as 3-methacryloxypropyltrimethoxysilane, mercapto-based silane coupling agents such as 3-mercaptopropyltrimethoxysilane, isocyanate-based silane coupling agents such as 3-isocyanatepropyltriethoxysilane, aminosilane-based coupling agents such as SH-6026 and Z-6050 manufactured by Dow Corning Toray Co., Ltd., and amino group-containing alkoxysilanes such as KP-390 and KC-223 manufactured by Shin-Etsu Chemical Co., Ltd. Among them, those having an organic functional group that reacts with the binder resin composition of the present crosslinked resin layer are preferred. The amount of the coupling agent added is preferably within a range of 0.01% by mass to 5.0% by mass based on the total mass of the binder resin composition.

[0120] The curing accelerator may be added in a required proportion of each component, such as a curing accelerator catalyst (e.g., N-ethylmorpholine, dibutyltin dilaurate, cobalt naphthenate, stannous chloride, etc.), an organic solvent (e.g., benzyl alcohol, etc.), a rust-preventive additive (e.g., zinc phosphate, iron phosphate, calcium molybdate, vanadium oxide, water-dispersed silica, fumed silica, etc.), an organic pigment (e.g., a phthalocyanine organic pigment, a condensed polycyclic organic pigment, etc.), or an inorganic pigment (e.g., titanium oxide, zinc oxide, calcium carbonate, barium sulfate, alumina, carbon black, etc.), so that crosslinking can be performed at a low temperature when crosslinking the crosslinkable resin composition.

[0121] (Amount of each ingredient) The ratio of the binder resin to the total solid components (100 parts by mass) in the crosslinkable resin composition is preferably 20 parts by mass or more, more preferably 30 parts by mass or more, while it is preferably 90 parts by mass or less, more preferably 80 parts by mass or less. When two or more types of binder resins are used in combination, it is preferable that the ratio of their total amount is within the above range. When two or more types of binder resins are used in combination, it is preferable that the ratio of their total amount is within the above range.

[0122] The ratio of the curing agent or crosslinking initiator to the total solid components (100 parts by mass) in the crosslinkable resin composition is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and even more preferably 20 parts by mass or more. On the other hand, the upper limit is preferably 80 parts by mass or less, more preferably 70 parts by mass or less, and even more preferably 60 parts by mass or less.

[0123] The ratio of solid components other than the binder resin and the curing agent or the crosslinking initiator to the total solid components (100 parts by mass) in the crosslinkable resin composition is preferably 0.01 parts by mass or more and 10 parts by mass or less, more preferably 0.1 parts by mass or more or 10 parts by mass or less, and even more preferably 1 part by mass or more or 10 parts by mass or less.

[0124] <Layer structure of this laminated film roll> The present laminated film roll only needs to have a configuration in which an anchor layer and an inorganic layer are laminated in this order on one side (referred to as the "front side") of the present base film, and may also have "other layers" such as a crosslinked resin layer on the back side of the present base film, between the anchor layer and the inorganic layer, or on the front side of the inorganic layer.

[0125] <Thickness of this laminated film roll> By adjusting the total thickness of the present laminated film roll, it is possible to ensure light transmittance while suppressing the occurrence of wrinkles, etc. From this viewpoint, the total thickness of the present laminated film roll is preferably 10 μm or more, more preferably 15 μm or more or 500 μm or less, even more preferably 20 μm or more or 250 μm or less, and even more preferably 23 μm or more or 125 μm or less.

[0126] <Characteristics of this laminated film roll> (Water vapor transmission rate (WvTR)) This laminated film roll has a water vapor transmission rate (WvTR) of 6.0 g / m at a temperature of 40°C and a relative humidity of 90%. 2 / day or less, preferably 4.0 g / m 2 / day or less, with 2.0 g / m being particularly preferred. 2 It can also be less than / day.

[0127] (Oxygen permeability) In addition, this laminated film roll has an oxygen permeability (cc / (m 2 24hr atm) to 6.0cc / (m 2 ·24hr·atm) or less, and preferably 4.0cc / (m 2 ·24hr·atm) or less, with 2.0cc / (m 2 ·24hr·atm) or less.

[0128] <Manufacturing method of the present laminated film roll> An example of a method for producing the present laminated film roll includes, but is not limited to, a method in which an anchor layer is formed on one side of a base film as necessary, and the present inorganic layer is formed on the surface of the anchor layer.

[0129] The anchor layer can be formed by applying the above-mentioned anchor coating agent to one side of the substrate film and drying it as necessary. As described above, the inorganic layer can be formed by, for example, physical vapor deposition (PVD), plasma-assisted vapor deposition, chemical vapor deposition (CVD), or a method in which inorganic particles are dispersed in an organic polymer and then applied.

[0130] <<This film laminate roll>> Next, as an example of an embodiment using the present laminate film roll, a film laminate roll using the present laminate film roll (referred to as the present film laminate roll) will be described. The present film laminate roll is a roll of a long film, but a film laminate obtained by cutting the roll to an appropriate size is similar to the present film laminate roll described below. Therefore, the present film laminate roll can be substituted for the film laminate in the following description.

[0131] An example of the present film laminate roll is the present laminate film roll, that is, a film laminate roll having a configuration in which an anchor layer and an inorganic layer are sequentially laminated on at least one side of the present base film (also referred to as "base film (1)"), and a base film (2) is bonded to the outermost surface, i.e., the surface of the present inorganic layer or the surface of the present crosslinked resin layer, via an adhesive layer.

[0132] <Base film (2)> As the base film (2), the base film (1), that is, the one explained as the present base film, can be used.

[0133] As the base film (2), a biodegradable film or a polyolefin film can be used.

[0134] The biodegradable film means a film having a layer containing a biodegradable resin as a main component resin, whether the film has a single layer structure or a multilayer structure. A film having a layer containing a biodegradable resin as a main component resin as a main layer is preferable. Among them, a film in which the main component resin of each layer is a biodegradable resin, whether the base film (2) has a single layer structure or a multilayer structure, is preferable.

[0135] Here, biodegradable resin means a resin that has biodegradability, and "biodegradability" refers to the property of ultimately being decomposed into water and carbon dioxide by the action of microorganisms, and preferably the property of satisfying the requirement that, in a pilot-scale aerobic composting environment at 58°C as described in ISO16929 or JIS K6952, within 12 weeks, 10% or less of a 100 mm square film remains on a 2 mm sieve. Examples of biodegradable resins include biodegradable aliphatic polyesters such as polylactic acid (PLA), polycaprolactone (PCL), polybutylene succinate (PBS), polybutylene succinate adipate (PBSA), polybutylene adipate, polyethylene succinate (PES), and 3-hydroxybutyrate-co-3-hydroxyhexanoate polymer (PHBH), and biodegradable aliphatic aromatic polyesters such as polybutylene adipate terephthalate (PBAT).

[0136] The polyolefin film used for the base film (2) is the same as the polyolefin film used for the base film (1).

[0137] The structure and thickness of the base film (2) are the same as those of the base film (1).

[0138] <Adhesive layer> The adhesive layer of the film laminate roll can be formed using a known adhesive composition. From the viewpoint of achieving both adhesiveness and barrier properties, it is preferable to use an adhesive composition containing a binder resin and a curing agent or a crosslinking initiator, and it is preferable to use, for example, a water-soluble epoxy resin, a water-dispersible polyurethane resin, or a water-dispersible urethane acrylate oligomer as the binder resin.

[0139] <Thickness of the film laminate roll> By adjusting the total thickness of the present film laminate roll, it is possible to ensure light transmittance while suppressing the occurrence of wrinkles, etc. From this viewpoint, the total thickness of the present film laminate roll is preferably 40 μm or more, more preferably 50 μm or more or 500 μm or less, even more preferably 50 μm or more or 250 μm or less, and particularly preferably 50 μm or more or 125 μm or less.

[0140] <Characteristics of this film laminate roll> (Water vapor transmission rate (WvTR)) This film laminate roll has a water vapor transmission rate (WvTR) of 3.0 g / m at a temperature of 40°C and a relative humidity of 90%. 2 / day or less, preferably 2.0 g / m 2 / day or less, and particularly preferably 1.0 g / m 2 It can also be less than / day.

[0141] (Oxygen permeability) In addition, the film laminate roll has an oxygen permeability (cc / (m 2 ·24hr·atm)) to 2.0cc / (m 2 ·24hr·atm) or less, and preferably 1.0cc / (m 2 ·24hr·atm) or less, with 0.5cc / (m 2 ·24hr·atm) or less.

[0142] <<Uses of this laminated film roll and this film laminate roll>> The laminate film roll and the film laminate roll can be cut to an appropriate size as necessary and widely used in applications requiring the blocking of various gases such as water vapor and oxygen, for example, as packaging materials requiring the blocking of various gases, for example, packaging materials for preventing deterioration of foods, industrial products, medicines, etc. In addition to packaging applications, the film roll and the film laminate are also suitable for various members such as liquid crystal display elements, solar cells, electromagnetic wave shields, touch panels, EL substrates, color filters, etc.

[0143] <<Explanation of terms>> In the present invention, the term "film" includes the term "sheet", and the term "sheet" includes the term "film". Furthermore, when the term "panel" is used, such as an image display panel or a protective panel, it encompasses a plate, a sheet, and a film. In addition, in the present laminate film roll or the present film laminate roll, the substrate film side is referred to as the lower side or back side, and the opposite side is referred to as the upper side or front side.

[0144] In the present invention, when it is described as "X to Y" (X and Y are any numbers), unless otherwise specified, it includes the meaning of "X or more and Y or less", as well as the meaning of "preferably larger than X" or "preferably smaller than Y". In addition, when it is stated that the amount is "X or more" (X is any number), it also means that the amount is "preferably greater than X" unless otherwise specified, and when it is stated that the amount is "Y or less" (Y is any number), it also means that the amount is "preferably smaller than Y" unless otherwise specified. EXAMPLES

[0145] The present invention will be specifically described below with reference to examples, although the present invention is not limited to the following examples in any way. The measurement and evaluation methods used in the present invention are as follows. For the laminate film rolls or laminate film body rolls produced in the following Examples and Comparative Examples, the laminate film or laminate film body was cut to an appropriate size and used as a measurement sample for the following measurement and evaluation methods.

[0146] (1) Tg of the base film Using a DSC measuring device (DSC204F1 manufactured by NETZSCH), measurements were made in the measurement temperature range of 0 to 200° C. at a temperature rise rate of 10° C. / min to determine the Tg (glass transition temperature) of the polylactic acid film (base film).

[0147] (2) Thickness of anchor layer The surface of the anchor layer was stained with RuO4 and embedded in epoxy resin. Then, sections prepared by ultrathin sectioning were stained with RuO4 again, and the thickness of the anchor layer was measured using a TEM (Hitachi High-Technologies Corporation "H-7650", accelerating voltage 100 kV).

[0148] (3) Thickness of inorganic layer formed by vacuum deposition (PVD) The thickness of the inorganic layer was measured using fluorescent X-rays. This method utilizes the phenomenon that when atoms are irradiated with X-rays, they emit fluorescent X-rays specific to the atoms, and the number (amount) of atoms can be determined by measuring the intensity of the emitted fluorescent X-rays. Specifically, two thin films of known thicknesses were formed on a film, and the specific fluorescent X-ray intensity emitted from each was measured, and a calibration curve was created from this information. The fluorescent X-ray intensity of the measurement sample was then measured in the same manner, and the film thickness was calculated from the calibration curve.

[0149] (4) Average linear expansion coefficient For the polylactic acid film or laminated film, TMA measurements were performed using a thermomechanical analyzer "TMA / SS7100" manufactured by Hitachi High-Tech Science Corporation at a heating rate of 2°C / min and a measurement temperature of 30 to 165°C, and the average linear expansion coefficients at 75 to 90°C, 90 to 105°C, and 105 to 120°C were determined, respectively.

[0150] (5) Water vapor transmission rate (WvTR) The laminated films obtained in the Examples and Comparative Examples and the film laminate obtained in Example 6 were used as measurement samples to measure water vapor transmission rate. The laminated film or film laminate was placed in a water vapor transmission rate measuring device DELTAPERM (manufactured by Technolox) with the laminated film facing the detector (the base film was exposed to water vapor), and the water vapor transmission rate (g / m2) was measured under conditions of a temperature of 40°C and a relative humidity of 90%. 2 / day) was measured.

[0151] (6) Oxygen permeability Except for the film laminate laminated with the biodegradable film in Example 6, the obtained laminated film was laminated with a non-oriented polypropylene film (CPP) to prepare a film laminate, which was used for measuring oxygen permeability. In accordance with JIS K 7126 B method, the oxygen permeability (cc / (m)) of each laminated film or film laminate was measured using an oxygen permeability measuring device (MOCON's "OX-TRAN 2 / 21 type oxygen permeability measuring device") at a temperature of 25°C and a relative humidity of 80%. 2 ·24hr·atm) was measured.

[0152] (7) Laminate strength A gas barrier laminate using a 60 μm thick non-axially oriented polypropylene (CPP) film ("P1146" manufactured by Toyobo Co., Ltd.) as a laminating film was cut into a 15 mm wide strip, and a portion of the edge was peeled off. Using a tensile tester ("STA-1150" manufactured by Orientec Co., Ltd.), the CPP film was peeled off at 180° at a speed of 300 mm / min to measure the laminate strength (g / 15 mm) after retorting. As in the measurement of oxygen permeability, for Example 6, the prepared film laminate (sample) was used as the measurement sample, and for the other Examples and Comparative Examples, measurement samples were prepared as described above.

[0153] (Preparation of polylactic acid film 1) For the first layer (top and bottom layers), 25% by mass of polylactic acid (trade name: NatureWorks 4032D, manufactured by Cargill Dow, USA) having structural units of L-lactic acid:D-lactic acid = 98.5:1.5 and a glass transition point (Tg) of 58°C, and 75% by mass of polylactic acid (trade name: NatureWorks 4060D, manufactured by Cargill Dow, USA) having structural units of L-lactic acid:D-lactic acid = 88:12 and a glass transition point (Tg) of 56°C were mixed, and 0.10 part by mass of dried granular silica (trade name: Silica 100, manufactured by Fuji Silysia Chemical Co., Ltd.) having an average particle size of 1.4 μm was mixed with the total of 100 parts by mass of polylactic acid, and the mixture was extruded into the top and bottom layers from a multi-manifold nozzle at 210°C while degassing using a 58 mmφ co-rotating twin-screw extruder. Furthermore, to form the second layer (middle layer), 100% by mass of a polylactic acid polymer having the structural units L-lactic acid:D-lactic acid = 98.5:1.5 (product name: NatureWorks 4032D, manufactured by Cargill Dow, USA) was extruded from the nozzle of a 75 mmφ co-rotating twin-screw extruder at 210°C to form the middle layer. The amount of molten resin discharged was adjusted so that the thickness ratio of the surface layer, intermediate layer, and back layer was 1:10:1. This coextruded sheet was quenched with a casting roll at about 35°C to obtain an unstretched sheet. Next, it was roll-stretched 2.5 times in the longitudinal direction at 76°C, and then stretched 2.9 times in the transverse direction at a temperature of 74°C with a tenter. The tenter had three equally spaced heat treatment zones, which were set to 90, 140, and 120°C in order, and the heat treatment time for the three zones combined was 30 seconds. Relaxation was performed by 4% in the third zone of heat treatment. Finally, it was cooled to produce a heat-treated film. The amount of molten resin discharged from the extruder and the line speed were adjusted so that the film thickness was 25 μm, thereby obtaining Polylactic Acid Film 1. The glass transition temperature (Tg) of the polylactic acid film 1 was 62°C.

[0154] (Preparation of polylactic acid film 2) For the first layer (top and bottom layers), 25% by mass of polylactic acid (trade name: NatureWorks 4032D, manufactured by Cargill Dow, USA) having structural units of L-lactic acid:D-lactic acid = 98.5:1.5 and a glass transition point (Tg) of 58°C, and 75% by mass of polylactic acid (trade name: NatureWorks 4060D, manufactured by Cargill Dow, USA) having structural units of L-lactic acid:D-lactic acid = 88:12 and a glass transition point (Tg) of 56°C were mixed, and 0.10 part by mass of dried granular silica (trade name: Silica 100, manufactured by Fuji Silysia Chemical Co., Ltd.) having an average particle size of 1.4 μm was mixed with the total of 100 parts by mass of polylactic acid, and the mixture was extruded into the top and bottom layers from a multi-manifold nozzle at 210°C while degassing using a 58 mmφ co-rotating twin-screw extruder. Furthermore, to form the second layer (middle layer), 100% by mass of a polylactic acid polymer (product name: NatureWorks 4032D, manufactured by Cargill Dow, USA) having the structural units L-lactic acid:D-lactic acid = 98.5:1.5 was extruded as the middle layer from the nozzle of a 75 mmφ co-rotating twin-screw extruder at 210°C. The amount of molten resin discharged was adjusted so that the thickness ratio of the surface layer, intermediate layer, and back layer was 1:10:1. This coextruded sheet was quenched with a casting roll at about 35°C to obtain an unstretched sheet. Then, it was roll-stretched 2.8 times in the longitudinal direction at 77°C, and then stretched in the transverse direction at 78°C with a tenter. The film was stretched 3.3 times at a temperature of 100°C. The tenter had three equally spaced heat treatment zones, which were set at 85°C, 115°C, and 100°C, respectively, for a total heat treatment time of 35 seconds. Relaxation was performed by 1% in the second heat treatment zone. Finally, the film was cooled to produce a heat-treated film. The amount of molten resin discharged from the extruder and the line speed were adjusted so that the film thickness was 25 μm, and polylactic acid film 2 was obtained. The glass transition temperature (Tg) of the polylactic acid film 2 was 62°C.

[0155] (Preparation of anchor coat solution 1) An anchor coat solution 1 was prepared by mixing an amorphous polyester resin (Vylon 200, manufactured by Toyobo Co., Ltd.) and an isocyanate compound (Coronate L, manufactured by Tosoh Corporation) in a mass ratio of 10:10.

[0156] (Preparation of anchor coat liquid 2) Anchor coat liquid 2 was prepared by blending an amorphous polyester resin (Vylon 200, manufactured by Toyobo Co., Ltd.) and an isocyanate compound (Coronate L, manufactured by Tosoh Corporation) in a mass ratio of 10:1.

[0157] (Preparation of anchor coat solution 3) An anchor coat solution 3 was prepared by mixing an acrylic polyol (Acrit 6AN-6000, manufactured by Taisei Fine Chemical Co., Ltd.) and an isocyanate compound (Coronate L, manufactured by Tosoh Corporation) in a mass ratio of 10:10.

[0158] (Preparation of Crosslinked Resin Layer Composition) 439.1g of hydrogenated XDI (1,4-bis(isocyanatemethyl)cyclohexane), 35.4g of dimethylolpropionic acid, 61.5g of ethylene glycol, and 140g of acetonitrile as a solvent were mixed and reacted for 3 hours under a nitrogen atmosphere at 70°C to obtain a carboxyl group-containing polyurethane prepolymer solution. Next, this carboxyl group-containing polyurethane prepolymer solution was neutralized with 24.0g of triethylamine at 50°C. 267.9g of this polyurethane prepolymer solution was dispersed in 750g of water using a homodisper, and a chain extension reaction was carried out with 35.7g of 2-[(2-aminoethyl)amino]ethanol, and acetonitrile was distilled off to obtain an aqueous dispersion of a polyurethane resin with a solid content of 25% by mass. 4% by mass of commercially available 3-glycidyloxypropyltrimethoxysilane was added to this aqueous dispersion to prepare a crosslinked resin layer composition.

[0159] <Example 1> One side of the polylactic acid film 1 was subjected to a corona treatment, and the anchor coating liquid 1 was applied to the corona surface and dried at 80° C. for 1 minute to form an anchor layer having a thickness (after drying) of 0.03 μm. Then, a vacuum deposition apparatus was used to deposit 2 x 10 -3 SiO was evaporated by heating under a vacuum of 10 Pa, and a SiO layer with a thickness of 30 nm was formed on the anchor layer. x A layer was formed to obtain a laminated film roll.

[0160] <Example 2> A laminated film roll was obtained in the same manner as in Example 1, except that the thickness (after drying) of the anchor layer was set to 0.10 μm.

[0161] <Example 3> A laminated film roll was obtained in the same manner as in Example 2, except that anchor coating liquid 2 was used instead of anchor coating liquid 1 in Example 2.

[0162] <Example 4> A laminated film roll was obtained in the same manner as in Example 2, except that anchor coating liquid 3 was used instead of anchor coating liquid 1 in Example 2.

[0163] <Example 5> In Example 1, SiO x A laminated film roll was obtained in the same manner as in Example 1, except that a crosslinked resin layer composition was applied onto the layer and dried at 100° C. for 1 minute to form a crosslinked resin layer having a thickness (after drying) of 0.5 μm.

[0164] <Example 6> The laminated film of Example 1 was laminated with a polybutylene succinate (PBS) film having a thickness of 30 μm as a laminating film to obtain a film laminate roll.

[0165] <Comparative Example 1> A laminated film roll was obtained in the same manner as in Example 1, except that the polylactic acid film 2 was used instead of the polylactic acid film 1 in Example 1.

[0166] <Comparative Example 2> A laminated film roll was obtained in the same manner as in Comparative Example 1, except that the thickness (after drying) of the anchor layer was set to 0.10 μm.

[0167] <Comparative Example 3> A laminated film roll was obtained in the same manner as in Comparative Example 1, except that the thickness (after drying) of the anchor layer was changed to 0.01 μm.

[0168] <Comparative Example 4> A laminated film roll was obtained in the same manner as in Example 1, except that the anchor layer was not formed.

[0169] <Evaluation Results> The properties of the polylactic acid film (base film), laminate film, and film laminate in the above examples and comparative examples are shown in Tables 1 and 2 below. As shown in.

[0170] [Table 1]

[0171] [Table 2]

[0172] <Consideration> It was found that in Comparative Examples 1 to 3, the average expansion coefficient of the laminated film did not satisfy the specified range, and therefore the barrier properties were deteriorated due to the influence of shrinkage of the laminated film. In Comparative Example 4, since no anchor layer was provided, the average expansion coefficient of the laminated film satisfied the specified range, but both the barrier properties and adhesion (lamination strength) were deteriorated due to the absence of the anchor layer. In contrast to this, in all of Examples 1 to 6, an anchor layer was present and the average expansion coefficient of the laminated film was within the prescribed range, so that both the barrier property and the adhesion property (lamination strength) were excellent.

[0173] From the above examples and the results of tests conducted by the inventors, the average linear expansion coefficient at 105 to 120°C in the longitudinal and transverse directions is -7 × 10 -4 ~0 / ℃ and -1×10 -3It was found that a laminated film with a temperature coefficient of 0 / °C or less can achieve both good barrier properties and adhesion (lamination strength).

[0174] The mechanism by which good barrier properties can be achieved (speculated) is that when deposition is performed on a substrate with low heat resistance, the substrate film tends to shrink due to the heat during deposition. On the other hand, when an anchor layer is present between the substrate film and the inorganic layer, the adhesion between the substrate film and the inorganic-containing layer is good, so the effect of the dimensional change (shrinkage or expansion) of the substrate film is directly transmitted to the inorganic layer, causing cracks and the like, which is thought to lead to a decrease in gas barrier properties. Therefore, it was thought that good barrier properties would be achieved by suppressing the average linear expansion coefficient to a certain level or less in the laminated film state after laminating the inorganic layer. As expected, in this laminate film, by controlling the average expansion coefficient of the base film and the laminate film comprising the anchor layer and inorganic layer within a certain range, the forces tending to shrink or expand in the base film and the laminate film themselves can be suppressed, thereby preventing cracks from occurring in the inorganic layer. It is presumed that this results in good barrier properties that can withstand heating during the processing step. [Industrial Applicability]

[0175] The laminated film roll and film laminate roll of the present invention can be widely used as packaging materials for packaging items that require blocking of various gases such as water vapor and oxygen, for example, to prevent deterioration of foods, industrial products, medicines, etc. In addition to packaging applications, they can also be suitably used for various members such as liquid crystal display elements, solar cells, electromagnetic wave shields, touch panels, EL substrates, color filters, etc.

Claims

1. A laminated film having a configuration in which an anchor layer and an inorganic layer are laminated in this order on at least one surface of a base film (1), The base film (1) is a polylactic acid film, The average linear expansion coefficient at 105 to 120°C in thermomechanical analysis (TMA) is -7×10 in the longitudinal direction. -4 0 / °C and -1×10 in the width direction -3 A laminated film roll having a temperature of 0°C or less.

2. The average linear expansion coefficient at 90 to 105°C in the thermomechanical analysis (TMA) is -5×10 in the longitudinal direction. -4 0 / °C and -3×10 in the width direction -4 2. The laminated film roll according to claim 1, wherein the viscosity is from 0° C. to 100° C.

3. The average linear expansion coefficient at 75 to 90°C in the longitudinal direction is -2 x 10 4 0°C or less and 0 to 2×10 -4 3. The laminated film roll according to claim 1, wherein the temperature is 100° C. or more.

4. 4. The laminated film roll according to claim 1, wherein the base film (1) has a glass transition temperature (Tg) of 55 to 65° C.

5. 5. The laminated film roll according to claim 1, wherein the anchor layer is a layer containing at least one resin selected from the group consisting of polyester, urethane resin, and acrylic resin as a main component resin.

6. 6. The laminated film roll according to claim 1, wherein the anchor layer is a layer containing an isocyanate compound.

7. The laminated film roll according to any one of claims 1 to 6, wherein the inorganic layer is a layer containing at least one inorganic compound selected from silicon oxide, silicon nitride, silicon oxynitride, silicon oxycarbide, silicon oxycarbonitride, aluminum oxide, aluminum nitride, aluminum oxynitride, and aluminum oxycarbide as a main material.

8. The laminated film roll according to any one of claims 1 to 7, further comprising a crosslinked resin layer on the inorganic layer.

9. 9. A film laminate roll comprising the laminate film constituting the laminate film roll according to any one of claims 1 to 8 and a base film (2) laminated together via an adhesive.

10. The film laminate roll according to claim 9, wherein the base film (2) is a biodegradable film.

Citation Information

Patent Citations

  • Polylactic biodegradable gas barrier film

    JP1998024518A

  • Vapor deposition film and packaging material using the same

    JP2000238172A

  • Polylactic acid film and laminate using it

    JP2004256795A

  • Biaxially oriented polylactic acid film for forming and container

    JP2004359948A

  • Polylactic acid-based film for decorating sheet, transfer foil, and decorating sheet

    JP2005015783A